OBTAINING AND CHARACTERIZATION OF NOVEL WOOD-POLYPROPYLENE COMPOSITES - Croitoru, Catalin; Patachia, Silvia; Pascu, Alexandru; Roata, Ionut Claudiu (Pro Ligno, 2016)
Wood Polymer Composites (WPCs) based on polypropylene (PP) have gained increasing interest over the past two decades, both in the scientific community and in industry. Meanwhile, a large number of publications is available, but yet the actual market penetration of such materials is rather limited. This paper aims to study an alternative method for compatibilization of wood with polypropylene, by using an innovative class of environmental-friendly additives, namely ionic liquids. To emphasize the performance characteristics of the various obtained composite materials bearing different wood to polymer ratios, water absorption, tensile mechanical tests, surface energy tests have been performed, indicating a good compatibility between the ionic liquid-additivated wood and the thermoplastic polymer.
Keywords: wood polymer composites; ionic liquids; surface energy; tensile tests; compatibilization